A comprehensive assessment of gray and white matter volumes and their relationship to outcome and severity in schizophrenia - Mitelman, Serge A. (2007)
Preliminary data suggest an association of posterior cortical gray matter reduction with poor outcome in schizophrenia. We made a systematic MRI assessment of regional gray and white matter volumes, parcellated into 40 Brodmann’s areas, in 104 patients with schizophrenia (51 with good outcomes, 53 with poor outcomes) and 41 normal comparison subjects, and investigated correlations of regional morphometry with outcome and severity of the illness. Schizophrenia patients displayed differential reductions in frontal and to a lesser degree temporal gray matter volumes in both hemispheres, most pronounced in the frontal pole and lateral temporal cortex. White matter volumes in schizophrenia patients were bilaterally increased, primarily in the frontal, parietal, and isolated temporal regions, with volume reductions confined to anterior cingulate gyrus. In patients with schizophrenia as a group, higher illness severity was associated with reduced temporal gray matter volumes and expanded frontal white matter volumes in both hemispheres. In comparison to good-outcome group, patients with poor outcomes had lower temporal, occipital, and to a lesser degree parietal gray matter volumes in both hemispheres and temporal, parietal, occipital, and posterior cingulate white matter volumes in the right hemisphere. While gray matter deficits in the granular cortex were observed in all schizophrenia patients, agranular cortical deficits in the left hemisphere were peculiar to patients with poor outcomes. These results provide support for frontotemporal gray matter reduction and frontoparietal white matter expansion in schizophrenia. Poor outcome is associated with more posterior distribution (posteriorization) of both gray and white matter changes, and with preferential impairment in the unimodal visual and paralimbic cortical regions.